Interspecific transgenic analysis of basal versus heat-shock-induced expression of a Drosophila pseudoobscura hsp82-neo fusion gene in D. melanogaster. - Sass, H. (Roux's Archives of Developmental Biology, 1994)
Drosophila melanogaster transformants containing a D. pseudoobscura hsp82-neo fusion gene were used to examine the relationship between chromosome structure and its variation to transcriptional activation and gene expression. At normal temperatures (25° C) transgenic hsp82-neo was transcribed in diffuse polytene chromosomal bands encoding antibiotic G418-resistance without intensive puff formation. Substantial basal expression of the transgene was observed in all tissues examined: salivary glands, brain, ventral ganglion, foregut, gastric caeca, midgut, imaginal discs, nurse cells and oocytes. In addition, basal hsp82-neo expression occurred throughout embryogenesis. In third-instar larvae subjected to optimal heat shock (36° C), novel heat-shock puffs at the transgene insertion sites in polytene salivary gland chromosomes resulted from a five-fold higher hsp82-neo transcription. Even at extreme heat shock (38° C) the transgene puffs corresponded to transcriptionally active sites. RNA probe protections showed that the natural intron of the D. pseudoobscura hsp82-neo transgene was efficiently removed from pre-mRNA by the D. melanogaster splicing machinery at 25-36° C. Upon extreme heat shock above 37° C intron splicing was inhibited. During recovery (25° C) from heat shock (36° C/20 min) the heat-induced hsp82-neo transcription was rapidly repressed and all novel transgene puffs regressed. The basal level of transcription of hsp82-neo pre-mRNA was restored within 1-2 h. The hsp82-neo mRNA returned to basal level within 3-4 h. Overall, these results demonstrate a conservation of cis-regulatory elements and trans-regulatory factors which is needed for faithful expression across the species barrier of the D. pseudoobscura hsp82-neo transgene in D. melanogaster.